'[...] wind in my hair, I feel a part of everywhere [...]': Creating dance for young audiences narrates emplacement. (1st July 2019) - Akinleye, Adesola
This article is a reflection from a moment during the tour of my performance work for young audiences – Found. I explore how the meaningfulness shared in the moments dancing together captures much broader narratives about the transformative connections of Being-in-Place: emplacement. I respond to Sarah Pink's call to explore bodily experiences through emplacement. Therefore, I use emplacement as a lens to theorize experiences during the practical performance work of Found, beyond the visual aesthetic of seeing live dance. This articulating and valuing the significance of where Self begins, or ends or is continuous in environment shares somatic inquiry with colleagues in architecture, social sciences and geography. I suggest ramifications on how dance offers corporeal dialogue that can empower children to take part in, and become aware of, their own presence in the co-created reality of Place.